Optimization of cryo-electron microscopy for quantitative analysis of lipid bilayers - Frederick A. Heberle; Doug Welsch; Haden L. Scott; M. Neal Waxham (Biophysical Reports, 2023)
Cryogenic electron microscopy (cryo-EM) is among the most powerful tools available for interrogating nanoscale structure of biological materials. We recently showed that cryo-EM can be used to measure the bilayer thickness of lipid vesicles and biological membranes with subangstrom precision, resulting in the direct visualization of nanoscopic domains of different thickness in multicomponent lipid mixtures and giant plasma membrane vesicles. Despite the great potential of cryo-EM for revealing the lateral organization of biomembranes, a large parameter space of experimental conditions remains to be optimized. Here, we systematically investigate the influence of instrument parameters and image postprocessing steps on the ability to accurately measure bilayer thickness and discriminate regions of different thickness within unilamellar liposomes. This unique application of cryo-EM places particular demands on image acquisition optimization and analysis due to the facts that 1) each vesicle is a different size with different curvature, 2) the domains in each vesicle can be heterogenous in size, and 3) the random orientation of vesicles amplifies the variability of domain size in projected images. We also demonstrate a spatial autocorrelation analysis to extract additional information about lateral heterogeneity.